Raman spectroscopy analysis of terra sigillata: the yellow pigment of marbled sigillata. (14th March 2016) - Wang, Tian; Sanchez, Corinne; Groenen, Jesse; Sciau, Philippe
Abstract : Raman spectroscopy combined with synchrotron radiation‐based techniques and electron microprobe was used to study the yellow component of slips of marbled sigillata. Electron microprobe analysis emphasized on a significant corpus that the yellow component was well made from a titanium‐rich clay preparation while X‐ray absorption near edge structure investigation at Ti K‐edge confirmed the massive presence of pseudobrookite (Fe2 TiO5 ) in good agreement with previous study. Raman spectroscopy was correlated with X‐ray absorption near edge structure results in order to extract the Raman spectra of pseudobrookite, which was compared with these ones of synthesized pseudobrookite powder reference. The investigation of a significant corpus (43 sherds) of marbled sigillata revealed that all samples exhibited similar Raman spectra in yellow zones attributable to the pseudobrookite structure. However, all spectra show the same features compared with the spectra of reference powder, that is, peak shifts and line broadenings, which could be related to Mg and/or Al substitutions in pseudobrookite crystals of marbled sigillata. The substitution plays a dual role in pseudobrookite structure: (1) stabilizes the structure through involving an increase of cationic disorder and (2) makes the color less dark and yellow, which could account for the nice yellow color of marbled sigillata. Copyright © 2016 John Wiley & Sons, Ltd. Abstract : Although the terra sigillata slip contains several phases, the high sensitivity of Raman spectroscopy to iron and titanium oxides allows us to focus on the pigment phase. Combing synchrotron‐based technique and Raman scattering, we identify the Raman spectrum of pseudobrookite. We show that the yellow color of Roman marbled sigillata is related to Al and/or Mg substitutions in pseudobrookite.